Quality of life among earthquake survivors living in prefabricated houses in Adıyaman: a cross-sectional study after the February 2023 earthquakes in Türkiye - Yusuf Emre Bostan; Yusuf Demirtaş (Frontiers in Public Health)
IntroductionOn February 6, 2023, two devastating earthquakes in Türkiye caused significant loss of life and widespread destruction, forcing many survivors into temporary housing. The earthquakes have the potential to significantly impact the quality of life of survivors, exacerbating various dimensions of their physical, emotional, and social well-being. This study aims to assess quality of life among earthquake survivors residing in prefabricated housing in Adıyaman, one of the most severely affected provinces, and to identify associated factors.MethodsThis cross-sectional study was conducted with 334 adult earthquake survivors residing in prefabricated housing in Adıyaman. Socio-demographic earthquake-related characteristics were recorded, and quality of life was assessed using the Short Form-36 (SF-36) through face-to-face interviews. The relationship between quality of life and independent variables was analyzed using the Mann–Whitney U test and multivariate logistic regression analysis.ResultsAll eight domains of the SF-36 showed a decline in comparison to general population norms. The smallest decrease was observed in the ‘physical functioning’ domain (7.6% in men and 15.4% in women), while the largest decline occurred in the ‘role limitations due to emotional problems’ domain (32.1% in men and 45.6% in women). Female gender, loss of a relative, hospitalization due to the earthquake, being married, being over 35 years old and having an education level below high school were identified as risk factors for scoring below the general population norms in at least one domain of the SF-36.ConclusionSixteen months after the earthquake, the quality of life among survivors remains significantly low, highlighting the critical need for the rapid implementation of targeted interventions, prioritizing high-risk groups.